Valoración de la flexibilidad isquiosural en empleados de la Universidad de San Buenaventura Seccional Medellín (Campus Universitario) y su implicación en los programas de prevención y promoción de la salud - Ortiz Muriel, Juan David (Educación, Ciencias Humanas y Sociales, 2018)
The present project was carried out with the intention of observing the state of flexibility of the employees of the San Buenaventura University (Campus). This observation sought to correlate the state of flexibility with its specific condition of labor mobility, in order to have objective tools in the development of health promotion and prevention programs through active breaks. It was carried out through a descriptive method with the use of Well analysis to measure flexibility and the IPAQ questionnaire (short) for the population grouping and data analysis, in which it was observed by means of the results For a group of sedentary people, there is no statistical relationship between their level of flexibility and the type of work motor skills they perform, for this reason it is believed that breaks can be made in a general way and without the need for a differentiation in the works of the factory. his work motor